The Effect of Using Folktales on Improving Reading Comprehension of the Tenth-Grade Students At MAN 1 Palu - Nuraisya Nuraisya; Sriati Usman; Desrin Lebagi; Muhammad Arid (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This investigation was conducted with the principal objective of examining the influence exerted by the utilization of folktales on enhancing the reading comprehension abilities of tenth-grade students at MAN 1 Palu. Employing a quasi-experimental methodology, the study encompassed two distinct cohorts: the experimental group, which engaged with narrative texts rooted in folktales, and the control group, which received instruction through conventional reading passages. The evaluative instruments comprised both pre-assessments and post-assessments, which incorporated multiple-choice items and essay prompts aimed at gauging comprehension at the literal level. Findings indicated that learners exposed to the folktale-based instructional approach exhibited a marked elevation in comprehension performance following the intervention. Specifically, the average achievement score within the experimental group rose from an initial mean of 28.21 to a post-treatment mean of 49.95. In contrast, the control group's mean score exhibited a modest increase, shifting from 28.45 to 30.05. Statistical validation using the Mann-Whitney U test produced a significance value of 0.007, thereby substantiating a statistically meaningful divergence between the two groups. This result necessitates the acceptance of the alternative hypothesis while concurrently rejecting the null. Consequently, it can be inferred that the incorporation of folktales into the reading curriculum substantively augments students’ literal reading comprehension capabilities in the context of tenth-grade learners at MAN 1 Palu.